The adventures of Sherlock Holmes - Doyle, Arthur Conan, Sir, 1859-1930 (Boston, Mass : Thomson Heinle, 2005)
Includes three Sherlock Holmes mystery adventures:'The Red-headed League,''The Adventure of the Speckled Band,' and'The Adventure of the Copper Beeches
Keywords: Holmes, Sherlock (Fictitious character) -- Fiction; Private investigators -- England -- Fiction; Detective and mystery stories, English; English literature